A scoping review on interventions to promote physical activity among adults with disabilities - Castro Serrano, Oscar (2016)
People with disabilities are at increased risk for obesity as well as other secondary conditions that lead to further decline in health and functional status. Despite there being strong evidence that physical activity (PA) can help to reduce the incidence and severity of preventable conditions, approximately half of all adults with disabilities get no regular physical activity. In addition, there is limited knowledge on the PA promotion interventions effectiveness among individuals with disabilities. Recently the Behaviour Change Techniques Taxonomy version 1 (BCT Taxonomy v1) became available as a method for reporting, replicating, and synthesizing research evidence, yet it is lacking in studies involving individuals with disabilities. The purpose of this study was to conduct a scoping review to examine the published literature on PA promotion interventions among adults with disabilities. A scoping review following the methodological framework provided by Arksey and O’Malley used electronic databases (Medline, PsycInfo and Cinahl), reference lists, and key journals to locate publications. Inclusion criteria were based on study aim, outcome measures, and a disability definition by the WHO International Classification of Functioning, Disability and Health. The BCT Taxonomy v1 was implemented to the PA promotion interventions. Of the 1822 articles initially identified, 38 articles from 37 studies met the inclusion criteria. A great number of studies based their PA measures solely on self-reported PA. Immediately following intervention, 69% of the studies reported a significant increase in PA behaviour. Although a similar percentage was reported in terms of achieved PA maintenance (66%), it should be noted that just nine studies included follow-up measures. Less than half of the studies reported a theoretical background to guide their intervention and 39 of the 93 BCTs composing BCT Taxonomy v1 were observed. The majority of the most coded BCTs belong to three categories: goals and planning (e.g.: action planning), feedback and monitoring (e.g.: feedback on behaviour), and social support (e.g.: social support (unspecified)). The amount of identified BCTs was related with the PA promotion intervention effectiveness. That is, the number of BCTs was greater for interventions achieving PA promotion than for interventions with no influence in PA behaviour. PA promotion interventions show promising results for a variety of disability conditions. The results from this scoping review highlight the need for future systematic reviews and meta-analyses in PA interventions among adults with disabilities. Following more rigorous guidelines and classifications (e.g.: ICF, CONSORT, BCT taxonomies) for designing, applying and reporting PA promotion interventions will benefit future reviewing efforts.